Konversi Modal dan Agensi Transpuan: Analisis Teori Pierre Bourdieu terhadap Eksistensi Pesantren Waria Al-Fatah Yogyakarta - Dewi Erlina; Rahmah Nur Sya'bani; Ika Arinia Indriyany (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
This study aims to analyze the existence of the Al-Fatah Transgender Islamic Boarding School in Yogyakarta through the lens of Pierre Bourdieu’s theory of social practice, with a focus on the dynamics of capital conversion and transgender agency. The central issue in this study is how marginalized groups, who often face religious and social exclusion, are able to maintain their living space amidst the dominance of patriarchal structures and religious conservatism. The method used is descriptive qualitative research, employing an in-depth literature review of various academic discourses on the relationship between gender and religion. The findings reveal that the existence of the Al-Fatah Islamic Boarding School is driven by the students’ success in converting cultural capital—specifically, inclusive theological knowledge—and social capital from advocacy networks into symbolic capital that legitimizes them as a religious student community. The agency formed through the accumulation of this capital enables transgender women to subvert the symbolic domination of society, while simultaneously negotiating their civic rights and access to worship independently and with dignity.